2015
DOI: 10.21101/cejph.a3931
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Taxi Accidents in Xi'an, China: What Matters Most?

Abstract: SUMMARYObjectives: Since the city of Xi'an has been extremely concerned with the serious problem of taxi involved crashes, injuries and fatalities, the primary purpose of this study is to identify the risk factors associated with the magnitude and nature of the problem and provide possible measures for enhancing the overall safety performance of taxi industry.Methods: Using 726 crash samples from the original of 7,183 observations in Xi'an over the period from 2006 to 2012, comparative statistics and systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
(23 reference statements)
2
7
1
Order By: Relevance
“…This study also revealed that foggy weather the condition was responsible for 35.2% of motor accident injuries. This nding is consistent with previous studies in Wolayta Ethiopia and China (20,27). It is also similar to a study done in Northern Ethiopia (18,28).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study also revealed that foggy weather the condition was responsible for 35.2% of motor accident injuries. This nding is consistent with previous studies in Wolayta Ethiopia and China (20,27). It is also similar to a study done in Northern Ethiopia (18,28).…”
Section: Discussionsupporting
confidence: 94%
“…A study was done in holy sodo also indicated that 72.5% of motorcycle accident injury was reordered by unlicensed riders (16).. Sixty-eight percent of motorcyclists had been involved in RTAs since they started riding (17)Environmentrelated factors like bad weather, tra c congestion or busy roads, and poor road conditions were associated with road tra c injury (12).. Rainy weather conditions were responsible for 13.8% of a road tra c accident (18,19).. Adverse weather conditions like rainy, foggy, and snowy days were a contributing factor for over 37% of the RTA (20).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of occupational health, taxi drivers have a higher body mass index (BMI) and more unhealthy eating habits due to the extended hours of driving, this finding confirms previous findings that musculoskeletal problems are common in this occupation [35]. Taxi drivers are vulnerable to other occupational exposures that affect their risk of being involved in road crashes, these exposures include vision defects [36], mental stress [37], irregular shi s [38], lower income [39], and traffic congestion conditions [40].…”
Section: Introductionsupporting
confidence: 79%
“…A number of strategies, such as the awareness of risks behaviors and periodical training, have been suggested for the prevention of taxi accidents in a study performed in China [33]. Another strategy suggested in this research is the provision of policies encouraging the taxi drivers to participate in exercises to keep healthy and reduce property damage accidents.…”
Section: Discussionmentioning
confidence: 99%